Sustainable materials for food packaging: influence of accelerated weathering exposure time on the properties of films based on polylactic acid and thermoplastic starch - Malbos, Luciana B.; Iglesias-Montes, Magdalena L.; Seoane, Irene T.; Cyras, Viviana P.; Manfredi, Liliana B. (Frontiers in Sustainable Food Systems, 2025)
This study aims to analyze the effects of accelerated weathering on the properties of films based on plasticized polylactic acid (PLA) and its blends with thermoplastic starch (TPS). The samples were collected and characterized at nine specific time intervals from 24 to 996 h. Changes in thermal and chemical properties were assessed by means of differential scanning calorimetry (DSC), thermogravimetry (TGA), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Moreover, variations in flexural mechanical properties, morphology, color, and transparency due to the accelerated weathering test were also investigated. It was observed that the molecular weight progressively decreased with increasing exposure time for all the samples and it was related to the deterioration of the mechanical and other physical properties of the weathered materials. PLA films showed a significant increase in crystallinity during the first 48 h of exposure in the chamber, which was consistent with the observed decrease in both transparency and ductility of the samples. The PLA/TPS films exhibited a higher susceptibility to degradation, resulting in their complete disintegration just 24 h after the weathering test began. All the samples were also placed under outdoor conditions and were collected for characterization up to 324 days of exposure. The neat and plasticized PLA films both exhibited an increase in crystallinity and opacity after 50 days of outdoor exposure, reaching levels comparable to those observed after 24–48 h in the more severe conditions generated by the combined variables of the accelerated weathering. Meanwhile, the neat TPS showed significant deterioration under environmental conditions, which directly contributed to the degradation seen in the PLA/TPS films. Therefore, PLA/TPS blends appear to be a promising material for single-use packaging applications, offering enhanced degradability and reduced costs compared to pure PLA-based films.